Impact of Scientific Findings on the Interpretation of the Holy Qrʼan - Thaib, Zamakhsyari Hasballah (Advances in Social Sciences Research Journal, 2023)
This paper aims to analyze the effect of scientific findings on the interpretation of the Qur'an. As the greatest miracle of the prophet Muhammad PBUH, the miracles of the Qur'an are not limited to a certain time and form or type. As divine words, there can be no conflict between true scientific facts and the revelation of Allah who is all-true. The interpretation of Salaf ulamâ’ is not infallible, preserved from mistakes. Correcting their views does not mean demeaning or insulting their position. The scientific discoveries put forward by the experts today are still potentially wrong in the future, therefore the interpretation of the Qur'an with scientific discoveries should not be forced. There are six effects of scientific findings that have had on the interpretation of the Qur'an; (a) the scientific findings corroborate one of the opinions put forward by ulamâ and clarify it, (b) scientific discoveries explain in more detail the opinion of one interpretation, (c) scientific discoveries provide some new interpretations, and the new interpretation is the more stronger, (d) scientific discoveries provide some new interpretations in addition to the other existing interpretations, where existing interpretations do not mutually interpret. This new interpretation did not become diligent, (e) scientific discoveries provide a new interpretation, but the interpretation is not stronger than the other existing interpretations, so, it becomes a distorted interpretation, and (f) scientific discoveries provide some new interpretations, and these new interpretations can be used as a basis for weakening and rejecting existing interpretations.